2020
DOI: 10.1111/1759-7714.13481
|View full text |Cite
|
Sign up to set email alerts
|

Impact of interstitial lung disease and simultaneous lung cancer on therapeutic possibilities and survival

Abstract: BackgroundFibrosing interstitial lung diseases (ILDs) are associated with poor survival and an increased risk of developing lung cancer (LC). Patient and LC characteristics, therapeutic possibilities and survival in this rare patient population are not well established.MethodsFibrosing ILD patients treated at the Department of Pulmonology Semmelweis University were reviewed retrospectively between 2012–2018 (N = 160). All patients with concomitant LC (N = 23) underwent detailed pulmonary evaluation. Cancer cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…The third variable for confirmed faster progression of PF-ILD in our patients was malignancy. Malignancy as a comorbidity is a serious complication associated with ILDs, especially in those showing progression as published previously in our previous study ( Barczi et al, 2020 ).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The third variable for confirmed faster progression of PF-ILD in our patients was malignancy. Malignancy as a comorbidity is a serious complication associated with ILDs, especially in those showing progression as published previously in our previous study ( Barczi et al, 2020 ).…”
Section: Discussionsupporting
confidence: 73%
“…At baseline and every follow-up, physical examination was performed, and a detailed medical history was taken with special emphasis on symptoms (dry/productive cough, sputum, and chest pain), respiratory infections, and comorbidities ( Barczi et al, 2020 ). In our clinical routine, studied autoantibodies were anti-nuclear antibodies (ANA), rheumatoid factor (RF), anti-cyclic citrullinated peptide antibodies (ACPA), anti-RNA polymerase, anti-centromere, anti-proliferating cell nuclear antigen (APCNA), anti-Ku, anti-P-ribosomal, anti-cytoplasmatic, anti-cytoskeleton, anti-chromatin, anti-Smith, anti-myeloperoxidase, anti-proteinase-3, anti-Jo-1, anti-SS-A, anti-SS-B, anti-SCL-70, anti-ribonucleoprotein (RNP), and anti-neutrophil cytoplasmic antibodies (ANCA).…”
Section: Methodsmentioning
confidence: 99%
“… 2 , 7 , 8 Therefore, patients with lung cancer and ILD often do not receive chemotherapy. 42 , 43 On the other hand, given evidence suggesting that chemotherapy may prolong survival, uniformly excluding these populations from chemotherapy may not be appropriate. 5 , 6 The present study showed that patients without sarcopenia were less prone to ILD exacerbation and could hence receive aggressive chemotherapy, which may contribute to a better prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…First, this was a single‐center retrospective study with a relatively small sample size, which may have introduced bias. However, lung cancer with ILD is a rare disease with a limited number of patients 3 , 4 , 9 , 10 , 12 , 13 , 14 , 42 , 45 The number of patients included herein does not considerably differ from those included in other studies. Moreover, given the absence of large‐scale phase III trials in patients with ILD‐complicated lung cancer to date, evidence has largely been obtained from retrospective studies.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, ILD is reported in 10%-30% of patients with lung cancer, [10][11][12][13][14][15] seriously affecting prognosis. 12,[16][17][18][19][20][21] This is because of the limited availability of effective chemotherapy approaches and exacerbation of treatment-related ILD. 5,18 Studies exclusively conducted in patients with small cell lung cancer (SCLC) have reported incidence rates of chemotherapy-triggered acute exacerbation (AE)-ILD ranging from 11.9% to 36.4%.…”
Section: Introductionmentioning
confidence: 99%